ANALISA KEBIJAKAN PARKIR OFF STREET DI PURWOKERTO - Sulfah Anjarwati (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2010)
At city purwokerto found more than 5 shopping centre not yet has representative parking place where parking place need and infrastructure that provided uneven and disagree with characteristics Parking. may even exist several shopping centre will not has this matter parking place cause shopping centre visitor will park the vehicle in area of around shopping centre or in road body. Durasi watchfulness result parking is got average long from each parking vehicle at study region during 1.53 clock. parking accumulation total and wheel vehicle volume four that use areal parking from clock 09.00 up to blow 22.00 1700 vehicles. all also has value pto smaller than 1, this mean opportunity soes capacity available that is 605 parking compartments too much compared with vehicle total parking, so that many parking compartments untapped. Key word: off street parking